2019
DOI: 10.1002/qua.26082
|View full text |Cite
|
Sign up to set email alerts
|

On topological indices of carbon nanocones and nanotori

Abstract: Let G be a graph with n vertices and d i is the degree of its ith vertex (d i is the degree of v i ). In this article, we compute the redefined first Zagreb index, redefined second Zagreb index, redefined third Zagreb index, augmented Zagreb index of graphs carbon nanocones CNC k [n], and nanotori [C 4 C 6 C 8 (p,q)]. Also, compute the multiplicative redefined first Zagreb index, multiplicative redefined second Zagreb index, multiplicative redefined third Zagreb index, multiplicative augmented Zagreb index of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 31 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…In [6], the authors obtained some of the new results for anticancer drugs by using the multiplicative topological indices. In [12], the author discussed carbon nanocones and nanotori by using some of the topological indices. erefore, in this paper, we obtain new results for OTIS networks by using some topological indices.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], the authors obtained some of the new results for anticancer drugs by using the multiplicative topological indices. In [12], the author discussed carbon nanocones and nanotori by using some of the topological indices. erefore, in this paper, we obtain new results for OTIS networks by using some topological indices.…”
Section: Introductionmentioning
confidence: 99%
“…Graph theory is applied broadly in the field of nanotechnology, specifically in nanostructures, in which carbon has been the central attention in the intense research activity [6][7][8]. Ge and Sattler discovered carbon nanocones (CNCs) in the year 1994 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies, such as those by Hui et al [15] and Jahanbani [16], have demonstrated the significance of using topological descriptors and entropies to predict physical properties. These studies employed the quantitative structure‐property relationship (QSPR) methodology, a widely recognized analytical approach for numerically characterizing molecular features.…”
Section: Introductionmentioning
confidence: 99%